The expected variation of random bounded integer sequences of finite length - Rudolfo Angeles; Don Rawlings; Lawrence Sze; Mark Tiefenbruck (International Journal of Mathematics and Mathematical Sciences)
From the enumerative generating function of an abstract adjacency statistic, we deduce the mean and variance of the variation on random permutations, rearrangements, compositions, and bounded integer sequences of finite length.